PECULIARITIES OF THE CLINICAL COURSE AND DIAGNOSIS OF VITAMIN B12 AND FOLATE DEFICIENCY ANEMIA IN PATIENTS WITH DIABETES MELLITUS - Solomenchuk, Tetiana; Drobinska, Nataliia; Makar, Oksana; Kobak, Liubov; Korniychuk, Iryna; Panasiuk, Mariia; Tsyhanyk, Lilia; Chmyr, Nataliya; Savchenko, Arkadii; Bazylevych, Andriy (Eastern Ukrainian Medical Journal, 2024)
Introduction. A typical manifestation of anemia is a decrease in the blood's hemoglobin content, which, in combination with the changes in the color index and other indicators of the blood, allows us to assume its nature. Deficiency of vitamin B12 and folic acid in patients with diabetes mellitus requires the attention of clinicians because it can be accompanied by usual clinical manifestations, but it may also disguise itself as other diseases and be pathogenetically related to them. It is extremely important to detect anemia caused by a deficiency of vitamin B12 and folic acid in time. Therefore, clinicians need to pay attention to the problem of comprehensive assessment of the condition of patients with diabetes mellitus and to the use of reliable diagnostic methods aimed at studying the status of vitamin B12 and folic acid.The aim of the study was to demonstrate the peculiarities of the clinical course and the patient's own experience in the diagnosis of vitamin B12 and folate deficiency anemia in a patient with diabetes mellitus.Materials and methods. A 77-year-old woman with diabetes mellitus was under our observation; at the time of hospitalization, she complained of dizziness, general weakness, episodes of loss of consciousness, yellowing of the skin and sclera, nausea, dry mouth, discomfort in the right hypochondrium, and weight loss over the last month. To establish the diagnosis, a thorough anamnesis was collected, a complex of laboratory and instrumental studies was performed, and related specialists consulted the patient. For the diagnosis of anemia, in addition to the usual complete blood count, the content of vitamin B12 and folic acid in the blood, as well as the concentration of methylmalonic acid in the urine and the content of homocysteine ​​in the blood were determined.Results and discussion. During the thorough examination, hyperchromic anemia, increased blood content of vitamin B12, folic acid, and homocysteine, and an increase in the concentration of methylmalonic acid in the urine were revealed. The patient had no damage to the nervous system, and damage to the gastrointestinal tract was manifested by gastric hyperplastic polyps. The patient's clinical diagnosis was verified, and treatment was prescribed, considering vitamin B12 and folate deficiency as well as the underlying pathology. A reticulocyte crisis was noted as a result of correct tactics. As a result of the treatment, her condition improved, and she was discharged from the hospital with a recommendation to continue treatment at home.Conclusions. A comprehensive approach, taking into account the peculiarities of the clinical course, the determination of vitamin B12, folic acid, as well as methylmalonic acid and homocysteine are decisive for the differentiation and diagnosis of vitamin B12 and folate deficiency anemia in patients with diabetes mellitus.